How do we treat psoriasis patients with hepatitis C infections in real-world situations? A retrospective analysis of 34 patients - Leena Chularojanamontri (2020)
© 2019, © 2019 Taylor & Francis Group, LLC. Background: There is still relatively limited data on psoriasis and hepatitis C virus (HCV) infections. Objective: This study investigated the clinical characteristics and treatment of psoriasis patients with HCV infections in real-world practice. Methods: Medical records of all psoriasis patients with HCV infections who attended the outpatient clinic at Siriraj Hospital over a 10-year period were retrospectively reviewed. Results: Of 34 patients, 26 and 8 patients were men and women, respectively with a mean age of 57.0 ± 8.7 (range, 42.2–77.2) years. The median age of psoriasis onset was 42.7 ± 12.7 (range, 8–67.25) years. With a median follow-up period of 13.6 years, cirrhosis and hepatocellular carcinoma were found in 67.6% and 29.4% of the patients, respectively. The interferon used for HCV treatment exacerbated the psoriasis in 20% of those patients. Conventional treatments and anti-tumor necrosis factors (anti-TNFs) were used in strict collaboration with hepatologists. No patients experienced a worsening of their HCV infection. Conclusion: Despite a limited number of patients, a male predominance and late-onset psoriasis were frequently observed. Although, interferon therapy for HCV can exacerbate psoriasis, it is not contraindicated. All conventional treatments and anti-TNFs can be used, provided that there is strict collaboration with hepatologists.